2021
DOI: 10.3390/genes12121875
|View full text |Cite
|
Sign up to set email alerts
|

The First Two Complete Mitochondrial Genomes of Neoephemeridae (Ephemeroptera): Comparative Analysis and Phylogenetic Implication for Furcatergalia

Abstract: Mayflies of the family Neoephemeridae are widespread in the Holarctic and Oriental regions, and its phylogenetic position is still unstable in the group Furcatergalia (mayflies with fringed gills). In the present study, we determined the complete mitogenomes of two species, namely Potamanthellus edmundsi and Pulchephemera projecta, of this family. The lengths of two mitogenomes were 15,274 bp and 16,031 bp with an A + T content of 73.38% and 73.07%, respectively. Two neoephemerid mitogenomes had a similar gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…4 ). The lowest nucleotide diversity in cox1 is in agreement with observations in most sequenced insect mitogenomes ( Ma et al 2019 , Ge et al 2021 , Li et al 2021 , Zhang et al 2022 ), which presumably accounts for its ability to provide reliable species identification.…”
Section: Resultssupporting
confidence: 82%
“…4 ). The lowest nucleotide diversity in cox1 is in agreement with observations in most sequenced insect mitogenomes ( Ma et al 2019 , Ge et al 2021 , Li et al 2021 , Zhang et al 2022 ), which presumably accounts for its ability to provide reliable species identification.…”
Section: Resultssupporting
confidence: 82%
“…Both maximum likelihood and Bayesian phylogenetic trees showed that Vietnamellidae was closely related to Ephemerellidae and had a distant relationship with Teloganellidae, which was consistent with the results of Cai et al [ 12 ], Gao et al [ 45 ], and Rutschmann et al [ 90 ]. Over the last few years, many scholars did not include sequences of Teloganodidae when constructing the phylogenetic tree within Ephemeroptera, so the sister clade of Vietnamellidae and Ephemerellidae were still supported [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Ogden et al combined the molecular data ( sRNA , IrRNA , 18S rDNA , 28S rDNA , and H 3 genes) and morphological data suggesting that Vietnamellidae, Teloganodidae, and Ephemerellidae were in a parallel relationship, and the phylogenetic relationships among them had not been effectively analyzed [ 29 ]. In recent years, Li et al [ 41 , 42 , 43 ], Zhang et al [ 44 ], Cai et al [ 12 ], and Gao et al [ 45 ] reconstructed the phylogeny of Ephemeroptera based on mt genomes, all of which supported the formation of sister groups between Ephemerellidae and Vietnamellidae.…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether variation in either P or O among species was related to floral display size, we used phylogenetic generalized linear mixed models (PGLMM). Such models account for nonindependence caused by phylogenetic relations by using a variable and flexible Brownian‐motion model of trait evolution (Li and Bolker, 2019). The inclusion of a phylogenetically driven correlation structure is recommended when there is a phylogenetic signal in the model residuals (Revell, 2010; Hansen, 2014) or when there is an improvement in model fit when considering phylogenetic relations (Shepherd and Klaere, 2019).…”
Section: Methodsmentioning
confidence: 99%